Effectiveness of Authentic Performance Methods for the Development of Musical Interpretation in Music Students - Oleksandr DEMIANCHUK; Larysa SOLIAR; Oksana LEHKUN; Olena SHEVTSOVA; Nataliia POSIKIRA-OMELCHUK (Studia Universitatis Babeş-Bolyai. Musica)
Authentic music contributes to the revival of cultural traditions, which requires the selection of the most favourable approaches to its reproduction. The aim of the work is to determine the effectiveness of authentic performance methods for the development of musical interpretation in music students. The research employed the following methods: observation, efficiency ratio, sampling ratio, and correlation index. The authors developed teaching methods that involved working with an authentic musical repertoire, developing the performance technique of music students. It was also planned to build the skills of performing authentic melodies with the use of various musical instruments. Digital applications Music Theory Companion, goodEar Pro were also used for training. The original performance of European authentic melodies was achieved at the highest level (7.5), which is related to the observance of the sequence of sounds. Achieving a higher level of performance of authentic Ukrainian melodies is associated with the creation of own variations (8.0), which contributed to emotional performance. It was established that the musical process had an impact on the of students’ musical thinking, independence skills, musical and rhythmic skills, understanding of cultural values, and development of intonation. Personal (0.93) and professional (0.90) skills were also developed during the educational process. The practical significance of the research is the identified most favourable approaches to the authentic reproduction of melodies. Research prospects may involve studying the quality of authentic melodies as a result of using different musical instruments.